Effect of Intravenous Recombinant Tissue-Type Plasminogen Activator in Patients With Mild Stroke in the Third International Stroke Trial-3: Post Hoc Analysis - Khatri, Pooja; Tayama, Darren; Cohen, Geoff; Lindley, Richard I.; Wardlaw, Joanna M.; Yeatts, Sharon D.; Broderick, Joseph P.; Sandercock, Peter (Stroke (1970), 2015)
BACKGROUND AND PURPOSE—Randomized trial evidence on the risk/benefit ratio of thrombolysis for mild stroke is limited. We sought to determine the efficacy of intravenous recombinant tissue-type plasminogen activator (IV r-tPA) in a subset of patients with mild deficit in the third International Stroke Trial (IST-3). METHODS—IST-3 compared IV r-tPA with control within 6 hours of onset in patients for whom IV r-tPA was considered promising but unproven. Analysis was restricted to subjects randomized within 3 hours of onset with a baseline National Institutes of Health Stroke Scale ≤5, pretreatment blood pressure <185/110, and no other r-tPA exclusion criteria. We compared r-tPA and control arms for primary (Oxfordshire Handicap Score [OHS] 0–2) and secondary (ordinal OHS and OHS 0–1) outcomes at 6 months. RESULTS—Among 3035 IST-3 subjects, 612 (20.2%) had an National Institutes of Health Stroke Scale ≤5; of these 106 (17.6%) met the restricted criteria. Allocation to r-tPA was associated with an increase in OHS 0 to 2 (84% r-tPA versus 65% control; adjusted odds ratio, 3.31; 95% confidence interval, 1.24–8.79) and a favorable shift in OHS distribution (adjusted odds ratio, 2.38; 95% confidence interval, 1.17–4.85). There was no significant effect of r-tPA on OHS 0 to 1 (60% versus 51%; adjusted odds ratio, 1.92; 95% confidence interval, 0.83–4.43). CONCLUSIONS—This post hoc analysis in a highly selected sample of IST-3 supports the rationale of A Study of the Efficacy and Safety of Activase (Alteplase) in Patients With Mild Stroke (PRISMS) trial—a randomized, phase IIIb study to evaluate IV r-tPA in mild ischemic stroke.